2002
DOI: 10.1093/ndt/17.10.1795
|View full text |Cite
|
Sign up to set email alerts
|

Aortic valve calcification is an independent factor of left ventricular hypertrophy in patients on maintenance haemodialysis

Abstract: Our findings show that aortic valve calcification is associated with LVH in chronic haemodialysis patients, probably because valve resistance to ventricular outflow is increased as shown by trans-aortic flow velocities and pressure gradients. The effect on LVMI is independent of PP, anaemia, and overhydration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
3
7

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 21 publications
1
13
3
7
Order By: Relevance
“…Our cross-sectional data also provided some suggestion that valvular calcification and the calcification milieu (inflammation and high Ca ϫ P) may represent part of the process linking loss of RRF and LVH in PD patients and warrant further longitudinal evaluation. In contrast to the study by Ventura et al (21) showing that increased transaortic flow velocities or pressure gradients promote LVH in hemodialysis patients with aortic valvular calcification and stenosis, our data suggest that the relationship between valvular calcification and LVH in PD patients is unlikely to be explained by valvular stenosis, because only one patient with valvular calcification had moderately severe aortic stenosis and none had mitral stenosis. As shown in our study, lower RRF, more inflammation as denoted by higher hs-CRP, and higher Ca ϫ P all were associated with valvular calcification and were each associated with greater LVMI.…”
Section: Discussioncontrasting
confidence: 99%
“…Our cross-sectional data also provided some suggestion that valvular calcification and the calcification milieu (inflammation and high Ca ϫ P) may represent part of the process linking loss of RRF and LVH in PD patients and warrant further longitudinal evaluation. In contrast to the study by Ventura et al (21) showing that increased transaortic flow velocities or pressure gradients promote LVH in hemodialysis patients with aortic valvular calcification and stenosis, our data suggest that the relationship between valvular calcification and LVH in PD patients is unlikely to be explained by valvular stenosis, because only one patient with valvular calcification had moderately severe aortic stenosis and none had mitral stenosis. As shown in our study, lower RRF, more inflammation as denoted by higher hs-CRP, and higher Ca ϫ P all were associated with valvular calcification and were each associated with greater LVMI.…”
Section: Discussioncontrasting
confidence: 99%
“…12,13 In HD population, some studies showed that BMI was positively correlated with LVH 14 as in general population, whereas other studies gave different results. 15 In our study, the patients with LVH had higher BMI than those without LVH. Multivariate linear regression showed that BMI was positively correlated with LVMI, and such a positive correlation was elucidated by multivariate logistic regression.…”
supporting
confidence: 45%
“…inflammation and high Ca  P) may represent part of the process linking loss of renal function and LVH in patients before dialysis therapy and warrant further longer period of observation. In contrast to other studies, 21,22 which showed that increased transaortic flow velocities or pressure gradients promote LVH in HD patients with aortic valvular calcification and stenosis, our data suggest that the relationship between valvular calcification and LVH in PD patients is unlikely to be explained by valvular stenosis, because neither patient had valvular stenosis. As shown in our study, disorders of balance of vasoactive substances, lower RRF, increase calcification markers, dyslipidemia, and anemia all were associated with valvular calcification and were each associated with LVH.…”
Section: Discussioncontrasting
confidence: 99%